2020
DOI: 10.1002/jdd.12179
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of technology‐enhanced learning to improve periodontics educational outcomes: A systematic review

Abstract: Objectives Technology‐enhanced learning (TEL) has been suggested as a suitable learner‐centered pedagogical approach in dental education. However, the results of TEL effectiveness in periodontics education are controversial. Therefore, this systematic review aimed to evaluate the effectiveness of TEL to improve educational outcomes in the periodontics field compared to traditional learning methods. Methods The search comprised randomized controlled trials (RCTs) and crossover studies that were related to perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 45 publications
(197 reference statements)
5
12
0
Order By: Relevance
“…Restorative dental tasks might offer the feasibility of customization of the required assignments, whereas other dental disciplines may require higher customization and knowledge to fulfill specific field's requirements. 90 Second, this review showed that HT was the most used technology, especially in tasks that require drilling and tooth preparations, which agree with Towers et al 6 HT offers an additional dimension to VR through the sense of touch and force feedback (FFB) of the different tooth-layered structure and bone. Thus, HT proved efficient in training junior dental students the hand-eye coordination and spatial reasoning skills.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Restorative dental tasks might offer the feasibility of customization of the required assignments, whereas other dental disciplines may require higher customization and knowledge to fulfill specific field's requirements. 90 Second, this review showed that HT was the most used technology, especially in tasks that require drilling and tooth preparations, which agree with Towers et al 6 HT offers an additional dimension to VR through the sense of touch and force feedback (FFB) of the different tooth-layered structure and bone. Thus, HT proved efficient in training junior dental students the hand-eye coordination and spatial reasoning skills.…”
Section: Discussionsupporting
confidence: 78%
“…Restorative dental tasks might offer the feasibility of customization of the required assignments, whereas other dental disciplines may require higher customization and knowledge to fulfill specific field’s requirements. 90 …”
Section: Discussionmentioning
confidence: 99%
“…We identified 318 discrete research questions posed in these 77 articles, from which we distilled a final list of 61 (19.2%) distinct questions covering 14 of the 16 subdomains of the above framework (Table 2; Multimedia Appendix 4 [11][12][13][14][15][16]32,34,[98][99][100][101][102][103][104][105][106][107]). Research questions that spanned multiple subdomains were assigned by investigator consensus to the most relevant single subdomain.…”
Section: Research Questions From the Included Systematic Reviewsmentioning
confidence: 99%
“…[42,71,98] Education (modality) What is the effectiveness of digital education (mixed or single modality) compared with nondigital education to deliver health professions education? [54,69,99,100] Education (modality) Can digital education complement (ie, blended) or substitute traditional education for health professionals? [46] Education (modality) Does digital simulation-based psychomotor skills training provide any benefit to the medical trainee?…”
Section: Classifying Research Questions Addressed By Existing Systema...mentioning
confidence: 99%
See 1 more Smart Citation